1996
DOI: 10.1093/humrep/11.3.595
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte morphology does not correlate with fertilization rate and embryo quality after intracytoplasmic sperm injection

Abstract: The fertilization rates and further development of 528 human metaphase II oocytes directly injected by a single spermatozoon were analysed with respect to their morphological features at the light microscopy level at the time of retrieval. The deviations of oocyte morphology which were most frequently observed, after removal of cumulus cells, were dark incorporations, dark zona pellucida, large perivitelline space, spots, vacuoles, refractile bodies and irregular shape. These deviations correlated neither with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
112
3
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(137 citation statements)
references
References 9 publications
8
112
3
10
Order By: Relevance
“…Nevertheless, more than half of all collected oocytes show at least one morphological abnormality [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, more than half of all collected oocytes show at least one morphological abnormality [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Human metaphase II oocytes have distinct morphological characteristics that may be indicative of quality and therefore used to predict implantation potential [21,[36][37][38][39][40][41][42][43]. For example, regular patterns of granularity have been observed in the oocyte cytoplasm and it has been suggested that these patterns correlate with oocyte quality [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Many other parameters have also been analysed in oocytes such as zona pellucida thickness, spindle birefringence and extracellular dysmorphisms [36,47,48]. Results vary as to whether distinct oocyte dysmorphisms have any relation to fertilisation and development rates, probably due to a discordance in the scoring of these dysmorphisms [50], although an effect on pregnancies is often noted [21,36,47,50].…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmadaki olguların ortalama yaş, vücut kitle indeksi, antral folikül sayısı, matür oosit sayısı ve stimülasyon süresi sı-rasıyla 31.5±4. 2 …”
Section: Bulgularunclassified
“…Oosit kalitesi polar cisimcik (PB), zona pellusida (ZP), perivitellin aralık ve oosit sitoplazma (OS) morfolojik özel-liklerine göre belirlenebilir diyenler olduğu gibi buna karşı çıkanlar da bulunmaktadır. [2,3] Yapılan çalışmala-rın bazıları oosit morfolojisinin fertilizasyon üzerine etkisi olmadığını, [4,5] bazıları da morfolojik özelliklerin fertilizasyonu ve embriyoner gelişimi etkilediğini bildirmektedir. [6,7] Morfolojik açıdan bakıldığında sitoplazmik granül, fragmanlı PB ve sitoplazmik vakuol varlığı oosit kalitesini bozmaktadır.…”
Section: Introductionunclassified